The Importance of the Effectiveness of Using Physical Activity in the Sustainable Development of Preschool Children (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article provides information on ways to effectively organize education physical classes in preschool educational institutions through correction and optimization of motor activity. Recommendations on the use of methods of national games are given.